2014
DOI: 10.1055/s-0034-1382960
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Antitumor Activity of a Novel Heteroglycan from Cultured Mycelia of Cordyceps sinensis

Abstract: A novel heteroglycan, Cordyceps sinensis polysaccharide 1 (molecular weight 1 17???105?Da), was isolated and purified from mycelia of the fungus C. sinensis obtained by solid-state culture. Structural characterization by chemical analysis, GC-MS, FTIR, and NMR spectroscopy showed that C. sinensis polysaccharide 1 was mainly composed of (1???6)-linked ?-D-Glc and ?-D-Gal, with minor ?-(1???4)-D-Xyl and ?-(1???4)-D-Man residues probably located in the side chains with a trace amount of ?-(1???3)-L-Rha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our results showed that some WCCPSs have an effect on colon cancer cells in relatively lower or similar concentrations than have been found in previous studies on different cancer cell lines, including colon cancer [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. For instance, Cheng et al showed that Ginseng PS (GPS) caused inhibition of human colon cancer HT-29 cells at 600 μg/mL [ 69 ], Ma and colleagues provided evidence that PS extracted from hawthorn ( Crataegus .)…”
Section: Discussionsupporting
confidence: 81%
“…Our results showed that some WCCPSs have an effect on colon cancer cells in relatively lower or similar concentrations than have been found in previous studies on different cancer cell lines, including colon cancer [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. For instance, Cheng et al showed that Ginseng PS (GPS) caused inhibition of human colon cancer HT-29 cells at 600 μg/mL [ 69 ], Ma and colleagues provided evidence that PS extracted from hawthorn ( Crataegus .)…”
Section: Discussionsupporting
confidence: 81%
“…The relative contents of the three polysaccharides are 25.64, 33.33 and 41.03%, respectively. So the average molecular weight of CSP is 1.53 × 10 4 kDa from linear regression of the calibration curve, while that of polysaccharide from cultured mycelia of C. sinensis was 117 kDa (Mei et al 2014). The polysaccharide purified from C. militaris fruit bodies had a molecular weight of 5.94 × 10 3 kDa .…”
Section: Molecular Weightmentioning
confidence: 97%
“…It consisted of (1 → 6)-linked α-D-Glc and α-D-Gal, with minor β-(1 → 4)-D-Xyl and β-(1 → 4)-D-Man residues presumably seated in the side chains with a trace quantity of α-(1 → 3)-L-Rha residue. In the assays of the restrained proliferation of sarcoma 180 cells, polysaccharide 1 showed significant activity and induced apoptosis in a dosage-dependent manner [ 80 ]. A novel polysaccharide CME-1 ( 116 ) was identified from C. sinensis , it was composed of mannose and galactose at a 4:6 molar ratio and its molecular weight was 27.6 kDa.…”
Section: Polysaccharidementioning
confidence: 99%